2020
DOI: 10.1371/journal.pone.0244152
|View full text |Cite
|
Sign up to set email alerts
|

Conditional cooperation in group contests

Abstract: In this paper we show experimentally that conditional cooperation, a phenomenon described in the private provision of public goods, is also present in group contests, where participants’ contributions to their group performance partially determines if they overcome a rival group. This environment allows us to identify new determinants of conditional cooperation. We observe conditional cooperation in successful groups and in groups where members contribute more than rivals (even if they lose), but it vanishes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
5
2
Order By: Relevance
“…These studies found that losers increased contributions when their group contributed less than the rival group (deserving losers) (Tan and Bolle, 2007;Kiss et al, 2020). On the other hand, for the victory condition, results differ between studies: while in one study winners acted as conditional cooperators (Kiss et al, 2020) in the other winners decreased contributions with and without monetary incentives (Tan and Bolle, 2007). Both results contrast with the increase in cooperation that we found.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…These studies found that losers increased contributions when their group contributed less than the rival group (deserving losers) (Tan and Bolle, 2007;Kiss et al, 2020). On the other hand, for the victory condition, results differ between studies: while in one study winners acted as conditional cooperators (Kiss et al, 2020) in the other winners decreased contributions with and without monetary incentives (Tan and Bolle, 2007). Both results contrast with the increase in cooperation that we found.…”
Section: Discussioncontrasting
confidence: 93%
“…This increment in cooperation is somehow contrary to the expectations from the biosocial model of status that postulates that losers should decrease their predisposition to compete again (Mazur and Booth, 1998), and then, to reduce cooperation in the next round, but instead, the increment of cooperation might represent an opportunity for losers to regain status (Daly and Wilson, 1988;Mehta and Josephs, 2006). Results regarding the victory condition were ambiguous: while in one study winners decreased donations (Tan and Bolle, 2007), in the other acted as conditional cooperators (Kiss et al, 2020), which are not expected responses in conventional approaches in which winners increase their competitive motivations (Mazur, 1985;Geniole et al, 2017). Consequently, due to the lack of consistency between empirical data and within theoretical predictions, our goal is to contribute to clarify the effect of competition outcome on male ingroup cooperation under intergroup conflicts.…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…However, many societal concerns require cooperation and decisions of not just two individuals 5 . Multipleplayer (or n-player) games have been studied extensively by researchers in various fields 12,26,[36][37][38][39][40] , especially in behavioural science 41,42 and other application areas 2,12,23,28,29,44,45 . The most studied n-player cooperative game is the public goods game (PGG) 32,41 , which is the n-player PD 32,33 .…”
mentioning
confidence: 99%